Developing Native-Like Listening Comprehension Materials Perceptions of a Digital Approach - Mulyono, Herri; Vebriyanti, Devi Nur (Journal of ELT Research, 2016)
This paper reported the attempt teachers did in developing native-like (NLS) listening materials for their EFL learners using a text-to-speech (TTS) technology. Observation was carried out to record teachers’ procedures for developing NLS materials. Interview with teachers were undertaken to explore their’ perceptions towards the NLS listening materials and the benefits they gained from developing instructional media using technology. In addition, a questionnaire was distributed to 65 eight-grade pupils to gather information related to their opinions regarding the listening materials developed and used by their teachers. The findings show that teachers and pupils responded positively towards the NLS materials for listening comprehension. In addition, teachers were found to have more confidence in teaching listening skill while using the technology. There are three conditions which endorse this teaching confidence: the suitability of instructional materials used with the learning curriculum and pupils’ level of English proficiency, teachers’ self-efficacy to the teaching task, and the integration of technology in classroom teaching. The study suggests that TTS system can be used as computer assisted language learning (CALL) application particularly in the development of listening comprehension materials. The study also confirms earlier studies that teacher professional development can be promoted through integrated training on technology for classroom use.